Development of an Efficient Account-Numbering Method - Trueman, Richard E. (Management Science, 1961)
The desirability of maintaining customer accounts in both alphabetic and numeric sequence is discussed. An account-numbering method is described which provides almost exact alphabetic and numeric sequencing even though the original file may grow by several hundred percent. The mathematical basis for the method is developed and an illustrative example shows how the method would be applied to the design of a particular account system.